HUBUNGAN SMARTPHONE ADDICTION DENGAN SIKAP APATIS SISWA SMP - Lestari, Fuji; Afdal, Afdal; Meivilona Yendi, Frischa; Dian Suri, Gusni (Penerbit Lafadz Jaya, 2025)
This study examines the relationship between smartphone addiction and apathetic behavior in junior high school students. Using a quantitative correlational method, a sample of 280 students was selected by simple random sampling. Data were collected through valid and reliable instruments, then analyzed using descriptive percentages and product moment correlations. The results showed that the level of smartphone addiction and apathetic behavior was in the moderate category with a percentage of smartphone addiction of 67.85% and apathy of 69.28%. There was also a positive and significant relationship with a correlation coefficient of 0.481, included in the moderate relationship category with a significance level of 0.000, which indicates that the higher the smartphone addiction, the higher the apathetic behavior of students. These findings serve as a reference for guidance and counseling services to reduce apathetic behavior due to smartphone addiction, one of the guidelines in providing guidance and counseling services in schools, especially in individual counseling services, group guidance, and information services to reduce smartphone addiction and prevent the emergence of apathetic behavior in students.